Efficiency Redefined: An ANP-Optimized Work Scheduling on Employee Productivity in the Manufacturing Industry - Muzakki, Ilham; Ambarwati, Rita (Jurnal Minds: Manajemen Ide dan Inspirasi, 2024)
Scheduling is one of the important factors that affect employee productivity in a company. PT Maspion, as one of the large companies with a large number of employees, faces challenges in optimal work scheduling to meet varied production needs. This study aims to optimize work scheduling using the Analytic Network Process (ANP) method by considering several dimensions of criteria such as consistency, predictability, adequacy, and control. The research method used is a descriptive quantitative approach with primary data obtained through interviews and questionnaires to 30 experts in the field of work scheduling. The results show that consistent, predictable, adequate, and controlled work scheduling can increase employee productivity and employee well-being. In conclusion, the application of the ANP method in work scheduling can help companies in increasing employee productivity and welfare.